Editorial: El humanismo desde sus configuraciones y re-configuraciones (2021)
“Today, when we speak of the Humanities, we no longer know what we are talking about. What belongs now to that proud and ancient word, to that arrogant term that enclosed in its bosom the conception of man? “ George Steiner, The Humanities The particularities of the times through which the human being has passed have determined the conceptions that he has been establishing on ideas, thoughts and notions, and have tried to have as an axis the value of man per se in the past, in the present and in the future. The humanities have had this as a premise and end, and have walked as a shadow attached to the human being while he projects himself with his gaze in permanent perspective. However, in the light of modernity and this digital age, the humanities are being questioned and confronted about their object of study and the end of their being as the pillar of many epistemic models. Transhumanism and post-humanism, which have been gradually modifying the conception of the human being, his cosmovision and his outlook, make us foresee that his future is more uncertain than ever, and that the unconditional shadow that the humanities were, is disintegrating in time and in permanent, accelerated and inevitable change. In this sense, there is talk of the need to teach about the four Cs: critical thinking, communication, collaboration and creativity, and how to apply them as skills for life and for adaptation in the face of change and for reinvention, since in the near future the physical structures, the cognitive ones, will change and be replaced by ultra-developed algorithms that will motivate parallel lives in cyberspace, emerging identities, hybrid genres, and sensorial experiences generated by computer implants that will question the certainties that configured us as beings of corporeality, sensations, desires, will and empathy. Since the first edition, Quaestiones Disputatae has sought to motivate and that motivate the humanities to offer their work as reflection on situations that put at risk the value and role of the humanities in human development. However, it cannot ignore the revolution that the entire planet   is going through and the impacts this is having on what we believed to be permanent and firm. This awareness must promote until the last moment actions of resistance and spaces of reflection that motivate us not to declare ourselves as fallen in front of the overwhelming realities that are more complex day by day recognizing and exalting the value of what is human. Thus, this edition opens up a wide range of topics that not only link the academic interests of our authors, but also invite us to value their analytical exercise and the visions that each one of them shares with us, those ideas and perspectives that open up the possibility of debate, from the complexity of the individual human being and in his or her collective being. Thinking, stopping in the midst of technological acceleration, reflecting on the silence of one’s own inner voice and taking time for introspection, that is what this issue’s themes invite us to do: The complexity of philosophy and its permanent search for existential and essential answers is directly related to the value of corporeality and to the value of the other in the construction of the subject and conditions the ways of teaching and learning, the way of coexisting with diversity, the awareness of a power that is now manifested in biopolitics and that does not leave aside the universal tendency of education for work, but that also seeks to rescue such work for human development. The perspectives of humanity, and even more so of the humanities, become light and unnecessary in a world that can come to replace the human being with the efficiency and perfection of technique materialized in algorithms and in artificial intelligence, which had value and which was the essence of a species that ceased to be special, unique and powerful, to become a model in disuse and which because of its imperfection was fully replaced by the desires for perfection, tangible in operating systems and in machines without humanity and without spirit. No entanto, à luz da modernidade e desta era digital, as humanidades estão a ser questionadas e confrontadas sobre o seu objecto de estudo e o fim do pós humanismo, que têm vindo a modificar gradualmente a concepção do ser como o pilar de muitos modelos epistémicos. O transhumanismo e o humano, a sua cosmovisão e a sua visão, fazem-nos prever que o seu futuro é mais incerto do que nunca, e que a sombra incondicional que as humanidades foram, está a desintegrar-se no tempo e em permanente, acelerada e inevitável mudança. Neste sentido, fala-se da necessidade de ensinar sobre os quatro Cs: pensamento crítico, comunicação, colaboração e criatividade, e como aplicá-los como competências para a vida e para a adaptação face à mudança e à reinvenção, uma vez que num futuro próximo as estruturas físicas, as cognitivas, mudarão e serão substituídas por algoritmos ultra-desenvolvidos que motivarão vidas paralelas no ciberespaço, identidades emergentes, géneros híbridos, e experiências sensoriais geradas por implantes informáticos que questionarão as certezas que nos configuraram como seres de corporeidade, sensaçãoes, desejos, vontade e empatia. Desde a primeira edição, Quaestiones Disputatae tem procurado motivar a reflexào sobre situações que poem en risco o valor e o papel das humanidades no desenvolvimento humano. No entanto, não pode ignorar a revolução que todo o planeta está a atravessar e os impactos que isto está a ter sobre sitações que acreditamos ser permanente e firme. Esta consciência deve promover até ao ultimo momento acções de resistência e espaços de reflexão que nos motive. Poem en risco o valor e o papel das humanidades o que a não nos declararmos caídos perante as realidades esmagadoras que são cada vez mais complexas e que motivem as humanidades a oferecer o seu trabalho como um sacrifício na tarefa de reconhecer e exaltar o valor do que é humano. Assim, esta edição abre uma vasta gama de tópicos que não só ligam os interesses académicos dos nossos autores, mas também nos convida a valorizar o seu exercício analítico e as visões que cada um deles partilha connosco, aquelas ideias e perspectivas que abrem a possibilidade de debate, a partir da complexidade do ser humano individual e no seu ser colectivo. Pensar, parar no meio da aceleração tecnológica, reflector sobre o silêncio da  própria voz interior e reservar tempo para a introspecção, é isso que os temas desta edição nos convidam a fazer: A complexidade da filosofia e a sua busca permanente de respostas existenciais e essenciais está directamente relacionada com o valor da corporalidade e do outro na construção do sujeito e condiciona os modos de ensino e aprendizagem, o modo de coexistir com a diversidade, a consciência de um poder que se manifesta agora na biopolítica e que não deixa de lado a tendência universal da educação para o trabalho, mas que também procura resgatar esse trabalho para o desenvolvimento humano. As perspectivas da humanidade, e ainda mais das humanidades, tornam-se leves e desnecessárias num mundo que pode vir a substituir o ser humano pela eficiência e perfeição da técnica materializada em algoritmos e em inteligência artificial, que tinha valor e que era a essência de uma espécie que deixou de ser especial, única e poderosa, para se tornar um modelo em desuso e que, devido à sua imperfeição, foi totalmente substituída pelos desejos de perfeição, tangíveis nos sistemas operativos e nas máquinas sem humanidade e sem espírito.